2013
DOI: 10.7167/2013/823638
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Solution of Liquid Solutes in Various Solvents

Abstract: e values of the heats of solution (2131 solutions) of different liquid solutes in organic and inorganic solvents were obtained from the literature data on the heat of mixing (Δ mix ) in the wide range of concentrations. e limit values of the heat of solution of a solute ( ) in a solvent ( ) (Δ soln ) were calculated from the limit data of the dependence Δ mix / versus at → 0 and the values of that of a solute ( ) in a solvent ( ) (Δ soln ) from the limit data of the dependence Δ mix / versus at → 0, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…41 It is evident from eqn (2), ( 3), ( 5) and ( 6) that the enthalpy of dissolution of an additive (DH diss additive ) is an important quantity to determine the step energy and rate of growth from a solution containing such an additive. The aqueous enthalpies of dissolution of acetone 111,112 and biuret 113 were À10.5 and À26.1 kJ mol À1 , respectively. Nevertheless, the dissolution enthalpy of biurea is not readily available in scientic literature, and as a result, we estimated the same from the aqueous solubility data, and it was found to be À28.0 kJ mol À1 .…”
Section: Resultsmentioning
confidence: 98%
“…41 It is evident from eqn (2), ( 3), ( 5) and ( 6) that the enthalpy of dissolution of an additive (DH diss additive ) is an important quantity to determine the step energy and rate of growth from a solution containing such an additive. The aqueous enthalpies of dissolution of acetone 111,112 and biuret 113 were À10.5 and À26.1 kJ mol À1 , respectively. Nevertheless, the dissolution enthalpy of biurea is not readily available in scientic literature, and as a result, we estimated the same from the aqueous solubility data, and it was found to be À28.0 kJ mol À1 .…”
Section: Resultsmentioning
confidence: 98%
“…Sorption in Polymers below and above T g and Thermodynamics of Liquid Solutions. Ample data on dissolution of low molecular mass compounds in polymers above their T g and some limited set of the data on bulk sorption in glassy polymers allow one to make a comparison with the numerous results of the study of sorption thermodynamics of organic compounds 73,74 and gases in liquids. 75 Different solvents can be divided into two classes.…”
Section: Polymers Above and Below The Glassmentioning
confidence: 99%
“…Few studies have reported the results of calorimetric investigations during electrolyte preparation for Li batteries. However, there is a long history of studying the thermochemistry of solution mixings, especially for water solutions [43][44][45] . Fig.…”
mentioning
confidence: 99%